The relationship between neuromyelitis optica spectrum disorder and autoimmune diseases - Lin, Jie; Xue, Binbin; Li, Jia; Xie, Dewei; Weng, Yiyun; Zhang, Xu; Li, Xiang; Xia, Junhui (Frontiers in Immunology, 2024)
Objective There have been reports of neuromyelitis optica spectrum disorder (NMOSD) coexisting with connective tissue disorders. The objective of this study was to describe the characteristics of NMOSD coexisting with autoimmune diseases (AID). Methods This retrospective study evaluated NMOSD patients with and without AID. The enrolled patients had at least one attack, with duration of more than 1 year. Data on the demographics, clinical features, and laboratory findings were assessed. The Poisson model was used to investigate the risk factors associated with the annualized relapse rate (ARR), whereas the Cox model was used to evaluate the risk factors for the first relapse. Results A total of 180 patients (154 women and 26 men) with NMOSD were identified: 45 had AID and 135 did not. Female patients had a higher prevalence of concomitant AID (p = 0.006) and a greater relapse rate within the first year. There were no statistically significant differences in the characteristics of patients. Kaplan–Meier analysis revealed that NMOSD patients with seropositive aquaporin 4 antibodies (AQP4-Ab; log-rank: p = 0.044), had a shorter time to relapse. Patients seropositive for AQP4-Ab (HR = 2.402, 95%CI = 1.092–5.283, p = 0.029) had a higher risk of suffering a first relapse, according to the Cox model. Patients with and without AID showed a similar declining tendency in terms of change in ARR throughout the first 5 years of the disease. The ARR was greater in the first year [incidence rate ratio (IRR) = 1.534, 95%CI = 1.111–2.118] and the first 2 years (IRR = 1.474, 95%CI = 1.056–2.058) in patients with coexisting AID diagnosis prior to the NMOSD onset. Conclusions Patients with NMOSD with coexisting AID had similar characteristics when compared with those without AID. NMOSD patients with AID diagnosed before onset had a higher risk of relapse in the early stage of the disease.